Digitalisasi Pelayanan Publik Desa Palewai Dengan Sistem Informasi Desa - Suharsono Bantun; Jayanti Yusmah Sari; Noorhasanah Z; Syahrul Syahrul; Arief Budiman (Faculty of Computer Science, University of Jember, 2021)
One of the basic functions of government is to provide public services. Even during the Covid-19 pandemic, these needs must still be met and optimally adjusted by service providers. The Palewai Village Office, is one of the local government agencies that does not escape its obligation to improve public service standards during this pandemic. However, based on observations, it was found that the performance of public services in the office was not optimal because population data processing was still manual and data storage media still used physical documents. Therefore, an online information system is needed that can provide clear and up-to-date information, as well as make it easier for people to fill out forms from anywhere so that there is no crowd in the service room. This study aims to develop a Website- Based Village Information System at the Palewai Village Office which will handle population data, services for making cover letters and distributing population data and current information for the community. The results of this study are a website-based village information system that can manage community data effectively and efficiently and can be accessed quickly and easily to provide information related to services at the Palewai Village office.